Potentially Pathogenic Leptospira in the Environment of an Elephant Camp in Thailand - Chaiwattanarungruengpaisan, Somjit (Trop Med Infect Dis, 2020)
Leptospira is the causative agent of leptospirosis, a globally emerging zoonotic disease. The infection is commonly acquired through contact with the contaminated environment. To extend the knowledge on environmental source of leptospirosis, we investigated the presence of Leptospira in an elephant camp setting where the interaction between humans, animals, and the shared environment occur particularly when engaging in recreational activities. In this study, a total of 24 environmental samples were collected from an elephant camp area in western Thailand. All samples were processed for Leptospira isolation using the EMJH medium. The identification of Leptospira species was carried out by partial 16S rRNA and secY gene sequencing. Of those 24 samples, 18 samples (75%) were culture-positive for Leptospira. The recovered leptospires were mostly derived from water and soil sampled from a river and a mud pond, the main areas for recreational activities. The majority of the isolates were classified into “Pathogens” clade (89%, 16/18) and more than half of the isolates (61%, 11/18) contained species of the “Saprophytes” clade. Notably, two soil isolates from the river beach sampling area were found to contain leptospiral DNA with high similarity to the pathogenic L. interrogans and L. santarosai. The evidence of diverse Leptospira species, particularly those belonging to the “Pathogens” clade, suggest that the shared environments of an elephant camp can serve as potential infection source and may pose a risk to the elephant camp tourists and workers.